INTRODUCING LIFE MAPS AS TECHNIQUE IN A SOCIAL GROUP WORK PROGRAMME FOR YOUNG ADULTS LIVING WITH HIV/AIDS - Herman Strydom; Alida Herbst (Social Work/Maatskaplike Werk, 2007)
The first literature regarding life maps was found in a philosophy textbook dated 1909. The focus of this book was the individual’s life (the map of life) and the correlation with happiness and contentment throughout one’s life span. This book indicated many links with life maps as described in this study. The following interesting topics (Lecky, 1909) are worth mentioning: Happiness is a condition of the mind; Contentment and the desire for progress and self-growth should be balanced; Life actions should be guided; There is an ending to life – namely death. The map of life could describe one’s being from birth to death, emphasising different events, people, attitudes, choices, problems/difficulties and biological processes